Association of Monoamine Oxidase A with Tumor Burden and Castration Resistance in Prostate Cancer - Meenakshi Meenu, MBBS, MD, DM; Vipin Kumar Verma, PhD; Amlesh Seth, MBBS, MS, MCh; Ranjit Kumar Sahoo, MBBS, MD, DM; Pooja Gupta, MBBS, MD, DM; Dharamvir Singh Arya, MBBS, MD, PhD (Elsevier, 2020)
Background: Metastatic burden and aggressive behavior determine severity stratification and guide treatment decisions in prostate cancer (PCa). Monoamine oxidase A (MAOA) may promote tumor burden and drug/castration resistance in PCa. A positive association will pave the way for MAOA inhibitors such as moclobemide for PCa therapy. Objective: To analyze MAOA in peripheral blood mononuclear cells qualitatively and p38, c-Jun N-terminal kinases, nuclear factor kappa B, and their phosphorylated forms, vascular endothelial growth factor (angiogenesis), transforming growth factor beta, interleukin 6, and tumor necrosis factor-α (cytokines), Bcl-2 associated X, B-cell lymphoma 2, and P53 (apoptosis), prostate-specific membrane antigen, and epithelial cell adhesion molecules (surface markers) in plasma of patients with PCa. Methods: This was a 1-year pilot study in which patients with PCa were recruited and stratified into 2 groups and subgroups: treatment-naive with (M1) (n = 23) or without (M0) (n = 23) bone metastasis; hormone-sensitive prostate cancer (n = 26) or hormone/castration-resistant prostate cancer (n = 26). MAOA was detected using ELISA and other proteins were detected using immunoblotting technique. Results: MAOA was detected in 8.6% of M0 compared with 30.4% of M1 patients, and in 7.7% of hormone-sensitive compared with 27% of hormone/castration resistant PCa patients, associating it with bone metastasis and castration resistance. Multivariable regression analysis showed a correlation of MAOA with serum prostate-specific antigen, a marker for progression in PCa (Pearson correlation coefficient r = 0.30; P < 0.01). In patients with positive MAOA, there was overexpression of p38, phosphorylated-p38, c-Jun N-terminal kinases, phosphorylated c-Jun N-terminal kinases, nuclear factor kappa B, phosphorylated nuclear factor kappa B, transforming growth factor beta, vascular endothelial growth factor, interleukin 6, tumor necrosis factor α, Bcl-2 associated X, B-cell lymphoma 2, prostate-specific membrane antigen, and epithelial cell adhesion molecule in M1 compared with M0 group patients, associating these proteins with tumor burden. Overexpression of Bcl-2 associated X, tumor protein 53, c-Jun N-terminal kinases, nuclear factor kappa B, transforming growth factor beta, vascular endothelial growth factor, and prostate-specific membrane antigen and underexpression of B-cell lymphoma 2 and phosphorylated nuclear factor kappa B were observed in hormone-sensitive prostate cancer compared with hormone/castration-resistant prostate cancer, associating these proteins with castration resistance. Conclusions: Association of key molecules of oncogenesis and metastasis with MAOA suggests that MAOA inhibitors such as moclobemide might be effective in the management of PCa.